Perencanaan Strategis Sistem dan Teknologi Informasi pada PT Arion Indonesia dengan Tahapan Anita Cassidy - Iman, Much. Okky Nur; Nurcahyawati, Vivine; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT ARION INDONESIA is a company engaged in the production as well as distributor of language laboratories, multimedia computer laboratory, as well as some educational equipment and software. Information systems and technology at PT ARION INDONESIA requires a system strategy planning and information technology in accordance with the company's business strategy. The purpose of this thesis is to make the planning of system strategy and information technology in harmony with business strategy. Analytical Process with Anita Cassidy stage is divided into 4 stages (visioning stage, analysis stage, direction stage, recommendation stage).Anita Cassidy's analysis of the visioning stage to identify the mission, vision, goals, objectives, and business processes, used in formulating the company strategy so that the output of the map strategy. stage analysis to get an objective view related to current corporate STI conditions as well as aligning business strategy with STI strategy so that the output strategy. After that, the direction stage to review the company's business objectives, and determine the direction of STI in order to help companies to achieve business objectives so that the output of STI that matches business goals and can be measured. stage recommendation to make STI project roadmap which contains about STI implementation, time of work, and cost summary so that output roadmap.The result of strategic planning of information system and PT Arion Indonesia With Anita Casidy stage that is: Produce 18 STI strategies that customize 19 business business strategies and adapt the company's business goals. Produce 35 applications that answer 17 company business goals, adjust critical success factors every business target, have targets and can measure and answer business processes of value chain. 35 applications have been clustered based on strategic application, high potential, operational key, support and risk identification, STI cost so as to make it easier to determine application priority to make STI project roadmap and STI investment feasibility. STI strategies and apps customize the organization. STI strategies and applications adjust human resources. STI strategies and applications adjust infrastructure. Strategy STI and external competitive adjusting applications.